Implementasi Rentang Gerak pada Lansia yang Dipasang dengan Alat Pacu Jantung Permanen: Studi Kasus - Nurul Hikmawati, Sri Rezeki; Sari , Citra Windani Mambang; Haroen , Hartiah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: A pacemaker is a medical device that is implanted to electrically treat chronic heart rhythm dysfunction so as to produce a good heart rhythm. Installing a pacemaker is a difficult decision for patients and causes anxiety regarding activities and lifestyle, so that individuals tend to remain silent and not carry out activities. Lack of physical activity will cause joint pain. Range of motion (ROM) exercises are effective in reducing joint pain in the elderly and safe in the elderly with heart problems. This study aims to describe the application of range of motion exercises in the elderly with permanent cardiac pacemakers. Case: A 90 year old female elderly woman in a nursing home complained of pain in both knee joints, pain like being pressed without any spread of pain, pain scale 7 (0-10), pain increased when the client moved, pain decreased when resting. The client does not take any medication to relieve the pain. Physical examination showed that the client's muscle strength was 4/5 in all extremities, uric acid levels were 7.5 mg/dL, assessment using a handgrip showed that the right hand was 16.9 (normal) and the left hand was 12.3 (weak). The client said he was anxious about moving his leg because of the pain. Conclusion: After 3 days of treatment, the elderly said the pain in both knee joints had reduced. Future research can examine further the application of ROM exercises to elderly people with other degenerative cases